P‐1.10: Solution‐processed metal oxide semiconductors fabricated with oxygen radical assisting perchlorate aqueous precursors through a new low‐temperature reaction route. (28th November 2018) - Gao, Peixiong; Lan, Linfeng
Abstract : In this report, an innovative and simple chemical route for fabricating MO semiconducting films at relatively low temperature without any fuel additives or special annealing methods is demonstrated. Different from combustion method, the precursor that we compound contains only two kinds of oxidizers. The precursor, which consisted of perchlorate, nitrate, and DI water, is easily converted into In2 O3 at an annealing temperature of 250 °C due to oxygen radical assisting decomposition and large amount of heat generation. It is found that perchlorate salt can decompose and form oxide film with high quality at lower temperature when assisted by nitrate salt. The optimized In2 O3 ‐TFT fabricated at 250°C via this precursor exhibits a saturate mobility of 14.5 cm 2 V −1 s −1 . Furthermore, this approach has been expanded to fabrication films at 350°C and attained improved performance.